Correlation of Vaccine Responses - Zimmermann, Petra; Ritz, Nicole; Perrett, Kirsten P.; Messina, Nicole L.; van der Klis, Fiona R. M.; Curtis, Nigel (Frontiers in Immunology, 2021)
Introduction: The humoral response to vaccinations varies widely between individuals. There is no data available on the correlation between responses to different vaccines. In this study, we investigated the correlation of antibody responses between routine vaccine antigens in infants. Methods: One and seven months after the 6-month vaccinations and one month after the 12-month vaccinations, antibody concentrations to diphtheria, tetanus, pertussis, polio (serotypes 1-3), Haemophilus influenza type b (Hib), 13 pneumococcal serotypes, meningococcus C, measles, mumps and rubella were measured using fluorescent bead-based multiplex immune-assays. For the correlation of antibody responses, Spearman’s rank correlation coefficients (ρ) with 95% confidence intervals (CI) were calculated between responses to each vaccine antigen. Results: The correlation between concentrations of antibodies to the 6-month vaccine antigens was higher one month compared to seven months after vaccination. The strongest correlations at both time points were observed between antibody responses to different polio serotypes, certain pneumococcal serotypes and between responses to diphtheria and pneumococcal (conjugated to a diphtheria toxoid) vaccine antigens. Correlation between responses to tetanus, Hib, pertussis, polio and other vaccine antigens were weak. The correlation between antibody responses to the 12-month vaccine antigens was weaker than to the vaccinations ending at 6 months of age, and there was a negative correlation between responses to measles, mumps, rubella vaccine and non-live vaccine antigens. There was only weak correlation between antibody responses to vaccines of the same type (e.g. polysaccharide or toxoid vaccines). Conclusion: Correlation between antibody responses to similar antigens in the same vaccine (such as different serotypes of a bacteria or virus), as well as responses to antigens conjugated to similar carrier proteins are strong. In contrast, correlation between responses to other vaccines are weak. Measuring antibody responses to one or a few vaccine antigens therefore does not offer a reliable surrogate marker of responses to unrelated vaccines.